PENGARUH LEVERAGE, EFEKTIVITAS ASSET DAN SALES TERHADAP PROFITABILITAS DAN PENGARUHNYA PADA NILAI PERUSAHAAN SEKTOR INDUSTRI KOMSUMSI DI BURSA EFEK INDONESIA PERIODE TAHUN 2014-2018 - Muhammad Syaiful; Ifayani Haanurat; Muryani Arsal (COMPETITIVENESS, 2020)
This study aims to determine and analyze the effect of leverage, asset effectiveness and sales on profitability and its effect on the company value of the consumption industry sector in the Indonesia Stock Exchange for the 2014-2018 period and to identify and analyze the variables that have a direct or indirect effect on price to book. value. This research has been conducted on the Indonesia Stock Exchange. The analytical method used in this research is quantitative method, through path analysis and SEM testing.The results of this study indicate that Debt to Equity has a significant positive effect on Return on Assets; Total Asset Turnover has a significant positive effect on Return on Assets; Sales have a significant positive effect on Return on Assets; Debt to Equity Ratio has a significant positive effect on Price to Book Value; Sales have a significant positive effect on Price to Book Value; Return on Asset has a positive effect on Price to Book Value; Debt to Equity Ratio has a significant positive effect on Price to Book Value through Return on Assets; Sales have a significant positive effect on Price to Book Value through Return on Assets. This also shows that in addition to increasing the company's profitability it can increase the company's stock price.Keywords: Leverage, Asset Effectiveness, Sales, Profitability, and Company Value.